Mineralogical and Geotechnical Properties of Subgrade Soils Along Failed Portions of Abavo-Urhonigbe Road, Western Niger Delta, Nigeria - F. C. Ugbe; O. F. Odibo; E. A. Emioge; A. A. I. Etobro; K. N. Nwakaji (Journal of Applied Sciences and Environmental Management, 2022)
This paper present the investigation of the possible causes of the incessant road failure associated with subgrade soils of the Niger delta using mineralogical and geotechnical properties assessment. Geotechnical investigation revealed clayey sand form the bulk of the subgrade soils composed generally of fine to medium grains with low to intermediate plasticity. Based on AASHTO the soil classifies as A-2 and A-6 with the granular soils being dominant. The average values obtained for California Bearing Ratio (CBR), maximum dry density (MDD), optimum-moisture-content (OMC) and shear strength are 19%, 1726 kg/m3, 15.70% and 286 KPA respectively. The angle of friction ranged from 180 to 250 indicates high presence of sand. X-ray diffraction analyses reveal the absence of expandable clay mineral. Collapse potential ranged from 1.3 to 10.8% indicating slight to severe collapse. High amount of settlement and field observation of intense failure revealed the soils as collapsible, particularly when inundated under poor drainage conditions. Thus, the road failures observed in the study are as a result of the soil inherent properties and the failure of design relative to the Region peculiar geomorphological and climatic conditions.